European Surveillance of Antimicrobial Consumption (ESAC): quality indicators for outpatient antibiotic use in Europe. Issue 6 (30th November 2007) - Coenen, Samuel; Ferech, Matus; Haaijer-Ruskamp, Flora M; Butler, Chris C; Vander Stichele, Robert H; Verheij, Theo J M; Monnet, Dominique L; Little, Paul; Goossens, Herman
Abstract : Background and objective: Indicators to measure the quality of healthcare are increasingly used by healthcare professionals and policy makers. In the context of increasing antimicrobial resistance, this study aimed to develop valid drug-specific quality indicators for outpatient antibiotic use in Europe, derived from European Surveillance of Antimicrobial Consumption (ESAC) data. Methods: 27 experts (15 countries), in a European Science Foundation workshop, built on the expertise within the European Drug Utilisation Research Group, the General Practice Respiratory Infections Network, the ESCMID Study Group on Primary Care Topics, the Belgian Antibiotic Policy Coordination Committee, the World Health Organization, ESAC, and other experts. A set of proposed indicators was developed using 1997–2003 ESAC data. Participants scored the relevance of each indicator to reducing antimicrobial resistance, patient health benefit, cost effectiveness and public health policy makers (scale: 1 (completely disagree) to 9 (completely agree)). The scores were processed according to the UCLA-RAND appropriateness method. Indicators were judged relevant if the median score was not in the 1–6 interval and if there was consensus (number of scores within the 1–3 interval was fewer than one third of the panel). From the relevant indicators providing overlapping information, the one with the highest scores was selected for the final set of quality indicators—values were updated with 2004 ESAC data. Results: 22 participants (12 countries) completed scoring of a set of 22 proposed indicators. Nine were rated as relevant antibiotic prescribing indicators on all four dimensions; five were rated as relevant if only relevance to reducing antimicrobial resistance and public health policy makers was taken into account. A final set of 12 indicators was selected. Conclusion: 12 of the proposed ESAC-based quality indicators for outpatient antibiotic use in Europe have face validity and are potentially applicable. These indicators could be used to better describe antibiotic use in ambulatory care and assess the quality of national antibiotic prescribing patterns in Europe.